Persepsi Pustakawan terhadap Transformasi Perpustakaan Berbasis Inklusi Sosial pada Dinas Perpustakaan dan Kearsipan Provinsi Maluku - Ruhukail, Cliff Johanes; Koerniawati, Tintien (UI Scholars Hub, 2021)
The library transformation based on social inclusion has a significant impact on librarians in developing, and improving the quality of the community life. This study focuses on the perceptions of librarians at Dinas Perpustakaan dan Kearsipan Provinsi Maluku regarding the strategy for implementing the library transformation based on the aspects of Connectivity, Content, and Human. The type of research is a descriptive study with a qualitative approach. Techniques of data collecting used observation, interviews, and documentation, and analyzed by using Miles and Huberman’s techniques (1992). The results show that it has not been maximally implementation related to the three aspects, namely (1) Connectivity: there is not enough service space available to support the needs of users; unavailable of Wi-Fi; the hours of library services have not been adjusted to the needs of users; inconsistently in evaluating user satisfaction. (2) Content: procurement of new library materials has not been carried out; lack of knowledge in using digital collections; library socialization has not been maximized. (3) Human: there is no equal distribution of education and training for librarians not expanded the partnership network yet. The strategy, which the librarians need are: enriching their knowledge in library services and promotions; evaluate user satisfaction as well as attending various trainings to increase themselves.